2020
DOI: 10.1002/ar.24532
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in zygapophysial joint cavities: A histological study of human fetuses

Abstract: Human zygapophysial joints (ZJ) have regional differences in shape and orientation during prenatal growth. However, there is limited knowledge of the synovial recess during fetal development. We examined sagittal and horizontal histological sections of the vertebral columns of 30 human fetuses at gestational ages of 8–37 weeks. Fetuses of all gestational ages had subaxial cervical articular processes that were thicker than in the thoracolumbar regions, and as large as the corresponding vertebral bodies. A smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…5). According to our previous study, it had been specifically found in the subaxial cervi-cal region [13]. The venous-synovial complex was usually seen at the anterior end of the cervical ZJ, and it seemed to be a transient morphology in late-stage fetuses and, pos- (4,5); at the joint (right), the lower vertebral element is located anterior to the upper adjacent vertebra.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…5). According to our previous study, it had been specifically found in the subaxial cervi-cal region [13]. The venous-synovial complex was usually seen at the anterior end of the cervical ZJ, and it seemed to be a transient morphology in late-stage fetuses and, pos- (4,5); at the joint (right), the lower vertebral element is located anterior to the upper adjacent vertebra.…”
Section: Discussionmentioning
confidence: 89%
“…In our recent study of the cervical vertebrae [11][12][13], we found that the morphology of the fetal cervical ZJ is markedly different than that of the adult cervical ZJ. The joint cavity is very large as it extends posteromedially along the vertebral lamina beyond the articular process.…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, using histological sections of human fetuses, this study aimed to 1) characterize the growing jugular process in fetuses and 2) examine the C1 nerve course near and around the RCLM. Our recent studies have revealed the topographical anatomy at the occipitovertebral junction in human fetuses [2,6,7,8].…”
Section: Introductionmentioning
confidence: 99%